Two modified colonoscopically guided fecal microbiota transplantation catheter placement methods: a retrospective study (with video) - Li, Xinxu; Liu, Qinghua; Wang, Yajing; Zhang, Hongrui; Wu, Zhi; Fan, Rui; Ma, Yuyi; Gong, Wei; Li, Xiaxi (Frontiers in Medicine, 2025)
IntroductionFecal microbiota transplantation (FMT) transfers fecal microbiota from a healthy person into a patient for the treatment of various diseases. This study introduces two modified colonoscopically guided fecal microbiota transplantation catheter placement methods and evaluates their effectiveness and safety in clinical use.MethodsThis study retrospectively reviewed medical records and corresponding endoscopist operational records of FMT patients at Shenzhen Hospital, Southern Medical University, from January 13, 2022, to July 26, 2024. The study analyzed 117 cases, divided into the Direct Loop Clamping (DLC) group and the Clip Loop Binding (CLB) group. The primary outcome was the catheter placement success rate. The secondary outcomes were operation-related times and adverse events.ResultsBoth groups achieved a 100% success rate in catheter placement. The two methods showed no significant differences in cecal intubation time, withdrawal time, and total operation time. What’s more, the CLB group had a slightly shorter time for the first endoscopic clip securement (median 1.8 min vs. 3.7 min, P = 0.006). There were no significant differences in the incidence of adverse events between the two groups, and no severe adverse events were reported.ConclusionBoth modified colonoscopically guided fecal microbiota transplantation catheter placement methods demonstrated safety and effectiveness in securing the FMT catheter, meeting the needs of patients requiring multiple FMT treatments over a short period. However, further validation through large-scale randomized controlled trials is needed.